Seismic hazard at the Rosebery mine - Knobben, C. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Various tools are available to geotechnical engineers in mines to assess the current seismic hazard, and changes to the seismic hazard over time. Although detailed analysis of seismicity is generally conducted by geotechnical engineers, a simplified approach needs to be applied for the reporting and communicating of the change in seismic hazard over time to management. As a result, management can make informed decisions on mining approaches, taking into consideration a seismic hazard that is relatable and applicable to the mining environment. A process for assessing the seismic hazard has been developed using a modification of work conducted on the seismic hazard scale in Western Australian mines, with relation to specific time periods, allowing seismic hazard to be quantified over time.